Rod-shaped Zn–Ag–In–Te nanocrystals with wavelength-tunable band-edge photoluminescence in the near-IR region. Issue 8 (8th February 2018) - Kameyama, Tatsuya; Sugiura, Kouta; Ishigami, Yujiro; Yamamoto, Takahisa; Kuwabata, Susumu; Okuhata, Tomoki; Tamai, Naoto; Torimoto, Tsukasa
Abstract : The bandedge PL peak wavelength of ZnTe–AgInTe2 solid solution nanocrystals was tunable in the near-IR region by changing their chemical composition. Abstract : Rod-shaped nanocrystals (NCs) composed of ZnTe–AgInTe2 solid solution ((AgIn) x Zn2(1− x ) Te2, ZAITe) were synthesized in a 1-dodecanethiol solution. The resulting ZAITe NCs of 4–5 nm in width and 16–18 nm in length showed exciton peaks in the absorption spectra, regardless of their composition. The energy gap was enlarged from 1.2 to 1.6 eV by decreasing the x value of the NCs from 1.0 to 0.25. A sharp photoluminescence (PL) peak was observed in each PL spectrum of the NCs with x values of 1.0–0.5, assignable to band-edge emission, while NCs with x = 0.25 showed an additional broad PL peak originating from the defect sites due to the increased non-stoichiometry of NCs. With a decrease in x from 1.0 to 0.25, the band-edge PL peak was blue-shifted from 1010 to 809 nm in the near-IR region, accompanied by a decrease in the corresponding PL quantum yield from 47% to 0.07% due to the diminution of radiative recombination rate.